Screening for Resistance to Pythium Root Rot among Twenty-three Caladium Cultivars - Zhanao Deng; Brent K. Harbaugh; Rick O. Kelly; Teresa Seijo; Robert J. McGovern (EDIS)
Pythium root rot, caused by Pythium myriotylum (Ridings and Hartman, 1976), is a very damaging disease to caladium plants (Caladium x hortulanum). Use of disease-resistant cultivars has been an effective and economically viable strategy for integrated management of major diseases in numerous crops. This strategy could be used to control pythium root rot in caladium if resistant cultivars could be identified or developed. In an evaluation of 19 major commercial cultivars, 'Candidum', 'Candidum Jr.', 'Frieda Hemple', and 'White Christmas' were found to have a moderate level of resistance to Pythium. To find more resistant cultivars, twenty-three additional commercial cultivars were screened using the same Pythium isolates, inoculation and evaluation procedures as described earlier (Deng et al. 2004). This document is ENH1008, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 27, 2005.